The applicability of valency grammar to different school contexts: opinions and proposals from linguists and teachers - Fiorella Nicolini; Maria Silvia Rati (Italiano a scuola, 2024)
The paper summarizes the salient points of the debate that involved experts and students during the meetings organized by the "Polo Linceo" of Calabria. The meetings, which started with the talks of illustrious linguists and experts of valency grammar, aimed not only to analyse the theories and teaching methods linked to valency grammar, but also – as can be seen from the title of the contribution, which takes up that of the Course – to investigate the actual applicability of the model to different school levels and different teaching contexts, highlighting its strengths and some problematic aspects.